Acute renal failure: methods of treatment in the intensive care unit - Zyga, Sofia; Sarafis, Pavlos; Stathoulis, John; Kolovos, Peter; Theophilopoulos, Dimitris (My University, 2009)
Patients who are treated in an intensive care unit (ICU) show the need of recovery of their renal function. The reason is that, in this particular cohort of patients, we have to maintain the necessary balance between body fluids, electrolytes, and acid-base, try to suspend further renal damage and purify the patient's blood to better accept the given therapy. In this paper, we try to demonstrate all the methods that can be used depending on the patient's condition, the therapist's preferences and the hospital's capabilities. © 2009 European Dialysis and Transplant Nurses Association/European Renal Care Association.
Keywords: Acute renal failure; Haemodialysis; Nursing